(untitled) (Universal International Scientific Journal, 2026)
This scientific article discusses the professional and personal image of a modern teacher, his role and importance in the educational process. It is argued that a modern teacher should not only have deep knowledge and methodological skills, but also have high culture, communicative competence, and the skills to effectively use information technologies. Also, the appearance of the teacher, speech culture, manner of communication, innovative approach, and social activity are analyzed as the main factors shaping his positive image. The topic reveals the role of the teacher’s image in strengthening the authority and trust of students, parents, and society in the modern educational environment.